Peles negras, páginas brancas: representação da pessoa negra no livro didático de história do 4° ano do ensino fundamental - CAVALCANTE, Elaine Rodrigues (2019)
This research puts into debate the representation of the black person in the textbook of the history discipline of the 4th grade of elementary school. In general, the objective is to analyze how the black person has been represented and what ideologies and stereotypes can be identified in this representation. It also has the perspective to discuss the implications of representation and ideologies in the identity construction of the black child, as well as the social effects that result from this visual and conceptual appropriation of the exposed material. It is a study of bibliographic and documentary character of qualitative approach, whose main source is the following textbooks: Projeto Buriti - Editora Moderna; Mundo Amigo - Editions SM; From School to the World - Attica Publisher. For analysis we resorted to assumptions of the technique of Content Analysis, which allowed us to understand the meanings hidden in the data raised. The results showed that the black person is represented in the 4th grade History textbook, mostly in a pejorative way in which his history, memory and identity are considered inferior to that of the white man and woman, the only holders of culture and knowledge. Blacks, in fact, are portrayed in most books analyzed as slave, labor, commodity, and product. Thus, there is the permanence of a traditional and excluding curriculum. Law 10.639 / 2003, although important to bring about changes in this regard and to question racial segregation, must indeed be implemented. It is concluded that textbooks need to be questioned, analyzed and criticized by teachers and students. Law 10.639 / 2003 is an indispensable element in this process, as this will set precedents for gradually overcoming the history of racial discrimination in Brazilian society.